Pengaruh Kompensasi, Lingkungan Kerja dan Gaya Kepemimpinan Terhadap Loyalitas Karyawan Pada PT. Enseval Putera Megatrading, Tbk. - Asnora, Fadzil Hanafi (Jurnal Manajemen Akuntansi (JUMSI), 2025)
The approach in this research is an associative approach. The population and sample used were 40 people using the Slovin formula. The data collection technique in this research uses a questionnaire. Data analysis techniques in this research use Validity, Reliability, Multiple Linear Analysis, Classical Assumption Test, t Test, F Test, and Coefficient of Determination. Data processing in research uses the SPSS (Statistical Package for the Social Science) software program version 16.00 for Windows. The results of this research prove that partially Compensation has a significant effect on Employee Loyalty, the Work Environment has no significant effect on Employee Loyalty and Leadership Style has a significant effect on Employee Loyalty, while simultaneously Compensation, Work Environment and Leadership Style have a significant effect on Work Loyalty at PT. Enseval Putera Megatrading, Tbk.